Research of Parametric Design System for Mould Head Based on Personalized Brassiere Customization (Journal of Fiber Bioengineering and Informatics, 2016)
The intimate apparel market is changing towards the personalized consumption environment rapidly. Onone hand, consumers' behaviour is more selective; On the other hand, brassiere design and developmentcycle are getting shorter and shorter. Mould head design is a key process in producing brassieres. Amaster cone which is the prototype of the mould head can be developed by a novel parametric method.The example-based method can easily make a new mould head style from several existing styles of mastercones only by adjusting corresponding weights. Through the remeshing and registration algorithm,designer can characterize the outer surfaces of the mould head and scanned bra cups, aligning themeach other at a point with same topology for assessing deviation. The results from this paper providea scientific, practical and effective solution for intimate apparel manufacturers so that they can improvethe development process of mould heads.
Keywords: Mould head; Foam; Bra cup; Conformity